Improving Critical Frequency of the Electrothermal V-Shaped Actuator Using the Particle Swarm Optimization Algorithm - Phuc Hong Pham; Phuc Truong Duc; Kien Trung Hoang; Ngoc-Tam Bui (Shock and Vibration)
This paper presents a thermal transfer model and optimization of a V-beam dimension to improve the critical frequency fC (i.e., expanding the effective working frequency range) of an electrothermal V-shaped actuator (EVA). The obtained results are based on applying the finite difference model, a method for calculating the critical frequency, as well as conditions to ensure the mechanical stability and thermal safety of EVA. The influence of beam dimensions (i.e., length L, width w, and incline angle θ of the beam) on the variation of critical frequency fC is investigated and evaluated. Moreover, the particle swarm optimization (PSO) algorithm is used to figure out the optimal beam dimensions aiming to increase the critical frequency while satisfying conditions such as mechanical stability, thermal safety, and suitable displacement of EVA. With the optimal dimensions of V-beam (L = 679 µm, w = 4 µm, and θ = 1.8°), the critical frequency of the V-shaped actuator can be achieved up to 136.22 Hz at a voltage of 32 V (average increment of fC is 33.1% with the driving voltage changing from 16 V to 32 V) in comparison with the nonoptimal structure (fC is only 102.34 Hz at 32 V).